2021
DOI: 10.1038/s41598-021-83587-1
|View full text |Cite
|
Sign up to set email alerts
|

A single-centre, retrospective study of the incidence of invasive fungal infections during 85 years of autopsy service in Brazil

Abstract: Autopsy continues to play an essential role in monitoring opportunistic fungal infections. However, few studies have analysed the historical trends of fungal infections in autopsies. Here, we analyse available data on fungal infections obtained from autopsy reports during 85 years of autopsies performed by the largest autopsy service in Brazil. All invasive fungal infections presented in autopsy reports between 1930 and 2015 were included. Of the 158,404 autopsy reports analysed, 1096 involved invasive fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Differentiation of species based on morphology only is not possible 26 . This perpetual dilemma results in underestimation of invasive fungal infections also in non‐pandemic times as several autopsy studies have shown 14,27 …”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of species based on morphology only is not possible 26 . This perpetual dilemma results in underestimation of invasive fungal infections also in non‐pandemic times as several autopsy studies have shown 14,27 …”
Section: Discussionmentioning
confidence: 99%
“…Hong et al also found that disseminated infection leading to sepsis correlated with an increased risk of death in mucormycosis patients [23]. Other studies have shown that other underlying conditions predispose individuals to the infection, including trauma, burns, intravenous drug use, use of broad-spectrum antibiotics, increases in iron or ferritin in the system, malnutrition, and use of voriconazole [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Some common predisposing factors include immunocompromised with neutropenia, organ or stem cell transplantation, renal insufficiency, broad spectrum antibiotics or prophylactic voriconazole, malnutrition, iron overload, prolonged use of steroids, and diabetes with or without ketoacidosis. [4] The prognosis is substantially better if the infection has not spread beyond the sinuses prior to the surgery. In local sinonasal disease, mortality has been reported as, 10 per cent.…”
Section: Introductionmentioning
confidence: 99%